Small bowel tuberculosis by multidetector CT enteroclysis - Ray, Dhirendra; Thukral, Brij B.; Gupta, Rohini; Chintamani; Prasad, Rajni (Japanese journal of radiology, 2013)
Purpose To prospectively evaluate the role of multidetector computed tomography (CT) enteroclysis in evaluation and diagnostic characterization of suspected small bowel tuberculosis. Materials and methods The study group included 21 human subjects suspected of having small bowel tuberculosis. A nasoenteric tube was positioned into the duodenojejunal junction under fluoroscopic guidance and water was infused by hand injection. After intravenous administration of 120 mL of iodinated contrast material, multidetector CT enteroclysis images were obtained with 40 × 0.625 mm collimation and findings were analyzed by three readers working in consensus. Findings were compared with the results of endoscopy, histopathological analysis, and clinical follow up. Results Multidetector CT enteroclysis was well tolerated in 20 patients; one of the patients complained of vomiting during intubation. Using multidetector CT enteroclysis diagnosis of abdominal tuberculosis was made in sixteen patients, out of which small bowel involvement was seen in 13 patients. Multidetector CT enteroclysis demonstrated Crohn’s disease in one patients and normal in four patients. The sensitivity and specificity in diagnosing abdominal tuberculosis by CT enteroclysis came out to be 93.75 and 100 % respectively. Conclusions Multidetector CT enteroclysis is well tolerable and accurate modality for evaluation and diagnostic characterization of small bowel tuberculosis.